Analisis Besaran Dividen Terhadap Besaran Laba Perusahaan - Hakim, Lukmanul; Ariffin, Muhammad (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Dividend amount is distribution of profit yielded by a company to the shareholders. The amount of dividend influences the amount of profit at the company.The objective of this research is to find out the amount of dividend distributed, how much profit is generated, and the influence of dividend and profit amount. The indicators are the dividend amount utilizes dividend in equity change statement and dividend per share (DPS), and the profit amount makes use of net profit in profit and loss statement and net profit margin (NPM). The data used are two companies running on the same consumers during six years – 2005 up to and including 2010.The method used is ratio dividend, to find out how much the dividend distributed and the profit ratio are, to know how much the profit earned by the company will be, and to detect the correlation between the two variables above. They have been processed utilizing SPSS 17.0. Based on the research yield, it can be concluded that the two companies have different correlation fact. There is positive correlation between dividend amount and profit amount at PT Mayora Indah Tbk., the dividend increase is followed by the profit increase due to the external factor, that is the debt has been empowered efficiently. The other way, there is negative correlation between dividend amount and profit amount at PT Delta Djakarta, that is the dividend increase does not followed by the profit increase due to the debt has not been empowered efficiently. Keywords:dividend amount; profit amount